Commerce in the Shadow of the Dutch Recomba: NV. Marba and Arab-Hadrami Capitalism in Semarang, 1946-1954 - Kemala Khoeronisa; Eka Yudha Wibowo (Universitas Hamzanwadi, 2026)
The development of NV. Marba in Semarang during the period 1946–1954 demonstrates a significant transformation in the pattern of Arab-Hadrami capitalism. The company was founded by Arab wholesale entrepreneurs from Surabaya with the support of strong social networks, as a response to post-independence economic constraints and an effort to resist the influence of the Dutch Recomba. This study examines the history of NV. Marba’s establishment and its role in the social and economic life of Semarang, focusing on the characteristics of Arab-Hadrami capitalism amid their position as a second-class group within the colonial stratification system. The research employs historical methods, including heuristics, source criticism, interpretation, and historiography, to trace the social networks and business activities of Faradj Martak and his associates. The findings show that NV. Marba was more than a trading office. It played a strategic role in local economic development through kapok trading, export-import activities, and the strengthening of industrial innovation. Socially, NV. Marba contributed through the recruitment of educated workers, sports activities, and participation in charitable initiatives, gaining public recognition. The study concludes that Arab-Hadrami capitalism evolved from simple commercial practices into industrial capitalism that supported economic stability and social sustainability in the post-independence period.